The Neighbourhood Improvement Plan: Montreal and Toronto: Contrasts between a participatory and a centralized approach to urban policy making - Filion, Pierre (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1988)
During the late 1960s and early 1970s the Canadian government effected a turnabout in its urban renewal policy, which culminated in the launching of the Neighbourhood Improvement Program in 1973. This program differed from prior forms of renewal by emphasizing the preservation of the built environment and citizen participation in neighbourhood planning. This article is concerned with examining the difference in the attitudes the city administrations of Montreal and Toronto took toward the federal program, and the impact of this difference on the results in the two cities. It appears that Toronto's mode of implementation was in the spirit of the federal policy revision while Montreal endeavoured to pursue traditional urban renewal objectives through its use of the program. These two approaches to the Neighbourhood Improvement Program are depicted respectively as expressions of a participatory and a centralized mode of policy making at the local level.